Solidification characteristics of Fe-Ni peritectic alloy thin strips under a near-rapid solidification condition - Chang-jiang Song; Yang Yang; Yuan-yi Guo (China Foundry, 2015)
This paper is an experimental investigation of the structure evolution and the solute distribution of 2 mm thick strips of Fe-(2.6, 4.2, 4.7, 7.9wt.%)Ni peritectic alloy under a near-rapid solidification condition, which were in the regions of δ-ferrite single-phase, hypo-peritectic, hyper-peritectic and γ-austenite single-phase, respectively. The highest area ratio of equiaxed grain zone in the hyper-peritectic of Fe-4.7wt.%Ni alloy strip was observed, while other strips were mainly columnar grains. The lowest micro-segregation was obtained in the Fe-7.9wt.%Ni alloy strip, while micro-segregation in the Fe-4.7wt.%Ni alloy was the highest. As opposed to the micro-segregation, the macro-segregation of all the Fe-Ni strips was suppressed due to the rapid solidification rate. Finally, the structure formation mechanism of Fe-Ni alloy strips was analyzed.